2022
DOI: 10.1002/1873-3468.14344
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of human glyoxalase I and its complex with TLSC702 reveal inhibitor binding mode and substrate preference

Abstract: Human glyoxalase I (hGLO I) is an enzyme for detoxification of methylglyoxal (MG) and has been considered an attractive target for the development of new anticancer drugs. In our previous report, the GLO I inhibitor TLSC702 induced apoptosis in tumor cells. Here, we determined the crystal structures of hGLO I and its complex with TLSC702. In the complex, the carboxyl O atom of TLSC702 is coordinated to Zn2+, and TLSC702 mainly shows van der Waals interaction with hydrophobic residues. In the inhibitor‐unbound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Forward and reverse primers used in the amplification procedure were 5′-ATCTTCGAA TCT GCCGTTATCGTAGATTTGAGAACTCA-3′ and 5′-AACGGC AGA TTCGAAGATCATATGTATATCTCCTTC-3′, respectively, containing a mutation site (underlined). Using the amplified fragment, the Seamless Ligation Cloning Extract (SLiCE) reaction [ 23 ] was performed at 37 °C for 20 min using a similar protocol to that described previously [ 24 ]. The SLiCE method is a seamless DNA cloning tool that utilizes homologous recombination activities in Escherichia coli lysates to assemble DNA fragments with approximately 15–19-bp homology lengths into a plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…Forward and reverse primers used in the amplification procedure were 5′-ATCTTCGAA TCT GCCGTTATCGTAGATTTGAGAACTCA-3′ and 5′-AACGGC AGA TTCGAAGATCATATGTATATCTCCTTC-3′, respectively, containing a mutation site (underlined). Using the amplified fragment, the Seamless Ligation Cloning Extract (SLiCE) reaction [ 23 ] was performed at 37 °C for 20 min using a similar protocol to that described previously [ 24 ]. The SLiCE method is a seamless DNA cloning tool that utilizes homologous recombination activities in Escherichia coli lysates to assemble DNA fragments with approximately 15–19-bp homology lengths into a plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…Using mRNA array screening, we found that glyoxalase I (GLO1) may be the most possible downstream effector of MALAT1. As reported, GLO1 is a ubiquitous enzyme involved in the detoxification of methylglyoxal (MGO) produced during tumor aerobic glycolysis [ 9 ], Methylglyoxal is an extremely cytotoxic metabolite that spontaneously glycates proteins and DNA, irreversibly forming toxic compounds called advanced glycation end products (AGEs) [ 10 ]. Glycation of DNA contributes to antiproliferative and apoptotic effects, and activates the DNA injury repair pathway to arrest the cell cycle, thus impairing tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the obstacles related to metabolic instability of GSH-based inhibitors, and to the violations of drug-like properties, some researchers have created non-GSHbased Glo-I inhibitors. 23,24 Natural flavonoids and anthocyanidins were investigated by Takasawa et al, as potential Glo-I enzyme inhibitors. 25 In order to identify crucial structural elements of flavonoids to serve as Glo-I inhibitors, computational and experimental approaches were performed by Al-Balas et al, where the structure-activity relationship (SAR) of a panel of 24 compounds belong to the flavonoid class of natural products, was explored.…”
mentioning
confidence: 99%